THE USAGE OF THE CRITICAL THINKING DEVELOPMENT TECHNOLOGY IN PREPARING OF FUTURE EDUCATORS OF PRESCHOOL EDUCATIONAL INSTITUTIONS TO FORMING THE SOCIAL COMPETENCE OF PRESCHOOLERS - Larysa Prysiazhniuk (Vasyl Stefanyk Precarpathian National University, 2018)
The article actualizes the problem of preparing future educators of pre-school education institutions in the context of the requirements of the Basic component of preschool education in Ukraine regarding the priority given to the social and moral development of the individual, the formation of the ability of children to reconcile personal interests with the collective. And, therefore, the author focuses on the need to form the readiness of future teachers to educate a socially competent preschooler. The author describes the definitions of "social competence of preschoolers", "teacher's readiness for the formation of the social competence of a child of preschool age", clarifies the peculiarities of the educational process regarding the social upbringing of children in a pre-school institution.The research presents the author's position regarding the technological support of the process of preparing future educators for a particular activity. In particular, the researcher emphasizes the necessity of introducing innovative methods and technologies into the educational process of the institution of higher education, which contributes to a conscious learning of students' educational information, provides for the development of their pedagogical thinking, projecting the professionalization of the acquired knowledge and skills. The author focuses on the technology of developing critical thinking, which implements a new educational strategy and provides a transition from reproductive to active learning. The researcher explores the possibilities of critical thinking strategies and techniques (Telegram of the text, Reading with the marking, Socratic Dialogue, Model 6W, Sincwein, tabular method, Romashka Blouma, etc.) in theoretical and practical training future educators to educate a socially competent preschooler. Key words: social competence of preschoolers, preparing future educators of preschool education institutions to forming the social competence of preschooler, system of higher pedagogical education, innovative educational technologies, critical thinking development technology